2020
DOI: 10.1111/ans.16087
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between computed tomography volumetry and nuclear medicine split renal function in live kidney donation: a single‐centre experience

Abstract: BackgroundPotential live renal donors undergo both renal computed tomography angiogram (CTA) and nuclear imaging dimercaptosuccinic acid (DMSA) scans. Each kidney's renal function and vascular anatomy influences the choice of donor side. Although DMSA measures differential blood flow, it is a surrogate for renal function and nephron mass. Computed tomography techniques can provide volumetry information. The aim of this study was to determine the relationship between measured split renal volumes on computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Finally, while RS was based on two methods, DTPA and MAG3, we deemed it reasonable to treat them equally when determining SRF. This decision was made due to the common utilization of both imaging tests in previous reports for measuring segmental renal function [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, while RS was based on two methods, DTPA and MAG3, we deemed it reasonable to treat them equally when determining SRF. This decision was made due to the common utilization of both imaging tests in previous reports for measuring segmental renal function [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in imaging technology have facilitated and improved volume measurement by computed tomography (CT) and magnetic resonance imaging (MRI) [9][10][11][12][13][14]. Several studies have shown that SRF can be more accurately determined by CT volumetry with automated measurement software than by RS [3, [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding volume measurements, 3D reconstruction and VR viewing allow for more precise volume measurements than 2D imaging can reliably provide. 12 With traditional 2D imaging, length, width, and depth of each kidney may be measured and multiplied to approximate the kidney's gross volume. Nuclear medicine imaging can be performed to measure the split function of each kidney but requires additional costly or inconvenient testing.…”
Section: Discussionmentioning
confidence: 99%